A Patient-Centered Forensic Nursing Model of Care for Victims of Law Enforcement Violence - Maija Anderson; Jacqueline Callari-Robinson; Margaret Glembocki; Elizabeth Louden (Health Equity)
Background: The manuscript examines the nature, manifestations, and potential causes of law enforcement violence as well the need for a model of care for victims. Specifically, it explores development of a preliminary forensic nursing model of care. The questions posed over the course of development of the model follow (1) What are the challenges to developing a rudimentary forensic nursing model of care for victims of law enforcement violence? (2) What are the tenets to be utilized in developing the model? (3) What additional recommendations are to be considered in refining and expanding the model? Key Concept: A review of the literature in forensic nursing found a gap in care for victims of law enforcement violence. To address the gap given the lack of research, a preliminary model of care was developed based on key constructs from the following established models: (1) Theory of Abolition, (2) Critical Race Theory, (3) Levels of Racism, (4) Intersectionality, (5) Social Determinants of Health, (6) Emancipatory Praxis – Theory of Forensic Nursing, (7) Trauma-Informed Model of Care, and (8) Patient-Centered Model of Care. Implications for practice: The preliminary model developed adheres to the International Council of Nurses guidelines, which emphasize the nurse’s duty to care without judgment or bias. Protocols established must be followed precisely to mitigate potential conflicts of interest in care of the victim. A practical application algorithm was developed based on care provided to other victims of violence. Conclusion: The model developed was focused on forensic nursing care. There is a need for further refinement involving an interdisciplinary approach. There is also a need for additional research as it relates to forensic nursing’s role in caring for victims of law enforcement violence.